Effect of testwiseness training on objective test performance in mathematics among secondary school students in Ekiti state (2012)
This study examined the effect of testwiseness training on objective test performance in mathematics among secondary school student in Ekiti State. The study employed a pre-test, post-test, control group quasi-experimental design with a 2x2x2 factorial matrix. A stratified random sampling was used to select 188 participants from four Senior Secondary Schools (two private schools and two public schools) in one local government areas in Ekiti state. The participants were randomly assigned to treatment and control groups. The treatment group was exposed to seven weeks training in testwiseness skills while participants in control group were not given treatment. Four hypotheses were tested at the 0.05 level of significance. Data were analyzed using Analysis of Covariance (ANCOVA). The results revealed that there was significant main effect of treatment on Mathematics achievement test scores of participants. There were no significant main effects of gender and school type on Mathematics achievement test scores of participants. There was also no significant interaction effect of treatment, gender and school type on Mathematics achievement test scores of participants. The study points to the need for Mathematics teachers to integrate Testwiseness training into the teaching of Mathematics.